EVALUASI KETIDAKSESUAIAN PENEMPATAN PEGAWAI DALAM JABATAN STRUKTURAL PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA DAERAH ISTIMEWA YOGYAKARTA - Rahmawati, Jatu; Novitasari, Dwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study was conducted to evaluate the discrepancy in the placement of employees in structural positions as well as to provide solutions to the factors causing the gap in the placement of structural positions. The main problems that are used as the focus of this research are: (1) The factors causing the incompatibility of structural position placement in the Regional Office of the Ministry of Law and Human Rights of the Special Region of Yogyakarta. (2) Knowing how to deal with inconsistencies in the placement of structural positions in the Regional Office of the Ministry of Law and Human Rights of the Special Region of Yogyakarta. The research method is descriptive-qualitative. Data was collected by means of observation, interviews, and documentation. The informen in this study were 10 (ten) structural echelon IV officials at the Regional Office of the Ministry of Law and Human Rights, Yogyakarta Special Region. Data analysis used qualitative analysis with reference to interview results and relevant secondary data support by mentioning the original source. The results showed that the implementation of the placement of employees in structural positions has not gone well. It can be seen that there are still positions that have not carried out education and training. The Regional Office of the Ministry of Law and Human Rights of the Special Region of Yogyakarta must prepare cadres or candidates for structural officials as an effort so that later there will be no gaps / incompatibility of positions.